Combining mercury thermoporometry with integrated gas sorption and mercury porosimetry to improve accuracy of pore-size distributions for disordered solids - Bafarawa, Buhari; Nepryahin, Artjom; Ji, Lu; Holt, Elizabeth M.; Wang, Jiawei; Rigby, Sean P. (Elsevier, 2014)
The typical approach to analysing raw data, from common pore characterization methods such as gas sorption and mercury porosimetry, to obtain pore size distributions for disordered porous solids generally makes several critical assumptions that impact the accuracy of the void space descriptors thereby obtained. These assumptions can lead to errors in pore size of as much as 500%. In this work, we eliminated these assumptions by employing novel experiments involving fully integrated gas sorption, mercury porosimetry and mercury thermoporometry techniques. The entrapment of mercury following porosimetry allowed the isolation (for study) of a particular subset of pores within a much larger interconnected network. Hence, a degree of specificity of findings to particular pores, more commonly associated with use of templated, model porous solids, can also be achieved for disordered materials. Gas sorption experiments were conducted in series, both before and after mercury porosimetry, on the same sample, and the mercury entrapped following porosimetry was used as the probe fluid for theromporometry. Hence, even if one technique, on its own, is indirect, requiring unsubstantiated assumptions, the fully integrated combination of techniques described here permits the validation of assumptions used in one technique by another. Using controlled-pore glasses as model materials, mercury porosimetry scanning curves were used to establish the correct correspondence between the appropriate Gibbs–Thomson parameter, and the nature of the meniscus geometry in melting, for thermoporometry measurements on entrapped mercury. Mercury thermoporometry has been used to validate the pore sizes, for a series of sol–gel silica materials, obtained from mercury porosimetry data using the independently-calibrated Kloubek correlations. The pore sizes obtained for sol–gel silicas from porosimetry and thermoporometry have been shown to differ substantially from those obtained via gas sorption and NLDFT analysis. DRIFTS data for the samples studied has suggested that the cause of this discrepancy may arise from significant differences in the surface chemistries between the samples studied here and that used to calibrate the NLDFT potentials.